Processing Factors and Risk Assessment of Pesticide Residues in Wine - Sandra Cermeño; José Manuel Veiga-del-Baño; Miguel Ángel Cámara; Pedro Andreo-Martínez; José Oliva (Fermentation, 2025)
The presence of pesticide residues in wine raises concerns about consumer health and regulatory compliance. This study evaluates the behaviour of seven pesticides (boscalid, penconazole, tebufenozide, kresoxim-methyl, trifloxystrobin, chlorpyrifos and lambda-cyhalothrin) during key stages of vinification, including clarification, fermentation, and racking, using liquid chromatography–tandem mass spectrometry. Penconazole, kresoxim-methyl and trifloxystrobin were not detected at the beginning of the vinification stage. Boscalid, chlorpyrifos and lambda-cyalothrin showed a reduction of 100% whit, a concentration below the limit of quantification at the end of the vinification stage. However, tebufenozide showed the lower elimination rate (88.1%), presenting a concentration at the end of the vinification process of 21.71 µg/kg. Experimental data confirm that pesticide concentrations progressively decline due to a combination of physicochemical transformations, adsorption onto solids, and biochemical processes. The clarification and racking stages are particularly important for reducing residues, primarily by removing suspended solids that adsorb pesticides. Fermentation also contributes to this reduction through microbial metabolism and enzymatic hydrolysis. The effectiveness of these stages depends on the pesticide’s solubility, chemical stability, and interactions with components in the wine matrix. Additionally, a risk assessment based on Acceptable Daily Intake and Estimated Daily Intake was performed to evaluate potential consumer exposure, showing lower risk for all pesticides studied. The findings emphasise the importance of optimising clarification and racking procedures, selecting effective fining agents, and refining filtration techniques to further enhance pesticide removal.